Secure Base Leadership in military training: enhancing organizational identification and resilience through work engagement - Navas-Jiménez, María C.; Laguía, Ana; Recio, Patricia; García-Guiu, Carlos; Pastor, Alberto; Edú-Valsania, Sergio; Molero, Fernando; Mikulincer, Mario; Moriano, Juan A. (Frontiers in Psychology, 2024)
Introduction This study examines the relationships between secure base leadership, organizational identification, and resilience among military cadets, utilizing the Job Demands-Resources (JD-R) model as a theoretical framework. Specifically, it explores the mediating role of work engagement in these associations within the context of military training. Methods A cross-sectional study was conducted with 363 cadets from the General Military Academy of the Army in Zaragoza, Spain. The sample comprised second-year cadets (n = 170; 46.8%) and third-year cadets (n = 193; 53.2%), with a gender distribution of 84% male and 16% female. Participants evaluated their section chief captains using the Leader as Security Provider Scale and completed validated questionnaires measuring work engagement, organizational identification, and resilience. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) to test the hypothesized relationships and mediation effects. Results The findings revealed that secure base leadership is positively associated with work engagement among cadets. Work engagement significantly mediated the relationships between secure base leadership and both organizational identification and resilience. The structural model explained a substantial proportion of variance in the outcome variables, supporting the applicability of the JD-R model in this context. Discussion These results underscore the importance of secure base leadership in promoting work engagement, which in turn enhances organizational identification and resilience among military cadets. The study highlights the role of leaders as secure bases in fostering personal and organizational well-being. Implications suggest that incorporating secure base leadership principles in military training programs could contribute to the professional development and overall well-being of military personnel.